2010
DOI: 10.1262/jrd.09-159s
|View full text |Cite
|
Sign up to set email alerts
|

Profiles of Circulating Steroid Hormones, Gonadotropins, Immunoreactive Inhibin and Prolactin During Pregnancy in Goats and Immunolocalization of Inhibin Subunits, Steroidogenic Enzymes and Prolactin in the Corpus Luteum and Placenta

Abstract: Abstract. The current study was performed to follow up the circulating hormonal changes and to correlate the findings with the physiological activity of the corpus luteum (CL) and placenta during pregnancy in goats. Blood samples were collected weekly from five goats during pregnancy for measuring steroid and protein hormones. A gradual increase was observed in immunoreactive (ir-) inhibin, with maximal levels at the 17th week. The plasma concentrations of estradiol and prolactin (PRL) showed nearly similar pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
11
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 56 publications
3
11
0
Order By: Relevance
“…The highhe highest levels of inhibin A were measured during the growth phase of the estrous cycle dominant follicles [14]. In golden hamsters, the ovarian follicles secrete large amounts of inhibin A and inhibin B during the second half of pregnancy [18], and the late stage of pregnancy in goats is associated with an increase in plasma ir-inhibin levels [13]. The present results show that both P450arom and 3βHSD expression in follicles is nearly stable in cyclic and pregnant goats ovarian follicles.…”
Section: Discussionsupporting
confidence: 46%
See 1 more Smart Citation
“…The highhe highest levels of inhibin A were measured during the growth phase of the estrous cycle dominant follicles [14]. In golden hamsters, the ovarian follicles secrete large amounts of inhibin A and inhibin B during the second half of pregnancy [18], and the late stage of pregnancy in goats is associated with an increase in plasma ir-inhibin levels [13]. The present results show that both P450arom and 3βHSD expression in follicles is nearly stable in cyclic and pregnant goats ovarian follicles.…”
Section: Discussionsupporting
confidence: 46%
“…Earlier studies showed that all luteal cells express P450arom without difference in affinity between the luteal phase and pregnancy, however, weak positive staining was observed in late pregnancy [31] and this was associated with an increase in plasma estradiol levels during mid pregnancy in goats [13]. On the other hand, 3βHSD showed a unique expression in luteal cells characterized by a gradual increase from the luteal phase to late pregnancy, with the maximum intensity being observed during late pregnancy.…”
Section: Discussionmentioning
confidence: 82%
“…Inhibins are produced mainly by the granulosa cells of ovarian follicles when the follicles develop from the small antral to preovulatory stages and suppress follicle stimulating hormone (FSH) secretion [12], such as in rats [10,13], golden hamsters [11,17], guinea pigs [19,20], sheeps [3], goats [7,8], monkeys [18], mares [15,16] and ducks [29,30]. Although changes in circulating inhibin in elephants have been reported [1,2], its cellular sources of ovaries have not been studied yet.…”
mentioning
confidence: 99%
“…Immunohistochemical analysis was conducted according to previously described methods [5,6]. Briefly, sections were incubated overnight at 4 C with the primary rabbit polyclonal antibody at a dilution of 1:1000.…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…After washing (as above), these sections were subsequently incubated with 2% (v/v) avidin-biotin complex (Elite ABC kit) in PBS at 37 C for 45 min and washed as above, and then the reaction products were visualized by treatment with 0.025% (w/v) 3,3′-diaminobenzidine tetrachloride (DAB; Sigma-Aldrich Co., St. Louis, MO, USA) in 0.01 M PBS containing 0.01% (v/v) H 2 O 2 for 1-20 min until a brown color developed. The specificity of each primary polyclonal antibody was examined as above but using normal rabbit serum instead of the primary antibody [5,6]. In order to identify the structural components and cell types within the ovaries, the sections were counterstained with hematoxylin (Wako Pure Chemical Industries, Osaka, Japan).…”
Section: Immunohistochemistrymentioning
confidence: 99%